Pathologic collision of urinary bladder urothelial carcinoma with small cell carcinoma: a case report - Wei Jiang; Chi Pan; Wei Guo; Zhen Xu; Qingtao Ni; Yashi Ruan (BMC, 2023)
Abstract Background Urothelial carcinoma is a major subtype of bladder cancer and small cell carcinoma (SCC) is a rare type of cancer in clinical practice. Pathologic collision of urinary bladder urothelial carcinoma with SCC is not common in clinical settings. Case presentation Here, we report a patient with high-grade papillary carcinoma which changed to collision tumor with SCC. The patient underwent radical cystectomy; however, neck and mediastinum lymph nodes metastases were detected 11 months after the operation. The lymph nodes were diagnosed pathologically as SCC. Chemoradiotherapy was subsequently prescribed. Unfortunately, this patient died of COVID-19 in early 2023. Discussion We hypothesized the mechanism underlying this pathological transformation. For patients with urothelial bladder cancer, pathological analysis should be conducted to allow standardized and persistent treatment. Moreover, drugs should be selected depending on the type of pathology, especially for patients who develop relapse, since collision tumor or other pathological tumors may be present. Conclusions We recommend that radical cystectomy be performed early enough for patients with non-muscle invasive bladder cancer, who are at a high risk of tumor recurrence. However, this conclusion needs to be validated in a larger number of patients.